The Nick of Time : Politics, Evolution, and the Untimely - Grosz, Elizabeth (Book collections on Project MUSE., 2004)
Prominent feminist theorist rethinks the relationship between evolution and the biological body through the study of three key figures: Darwin, Nietzsche and Bergson.